Chronic energy deficiency in young pregnant women in rural Indonesia: an analysis of basic health survey 2018 - Kuntari, Titik; Utami, Utami; Widyasari, Vita; Supadmi, Sri; Choironi, Emi Azmi (Universitas Airlangga, 2024)
Introduction: Chronic energy deficiency (CED) significantly impacts maternal health and child development. Socioeconomic conditions and access to health services cause young mothers in rural areas to have different health problems from those in urban areas. The study aimed to analyze the factors associated with CED among young pregnant women in rural areas in Indonesia. Methods: Secondary data for this cross-sectional study were obtained from the 2018 Basic Health Research Survey. One thousand one hundred and thirty-nine pregnant women aged <25 years were involved as subjects. Age, number of family members, education, occupation, gravida, abortion, supplementary feeding, and iron tablets during pregnancy were included as independent variables. Binomial logistic regression analysis was performed to measure the association between the independent and dependent variables. The strength of the association was expressed by p-value <0.05. Results: The three factors associated with CED were age (p=0.001), education (p=0.013), and supplementary feeding (p<0.001). Conclusions: Equitable education, increasing the age at which moms can become pregnant, and efforts to fulfill the nutrition needs of pregnant women by providing supplemental food based on community empowerment are significant. Family and community involvement will ensure the sustainability of this CED prevention program.